Psychiatric nurse practitioners' experiences of working with mental health care users presenting with acute symptoms - Kgalabi J. Ngako; Elsie S.J. van Rensburg; Sanah M.L. Mataboge (AOSIS, 2012)
Psychiatric nurse practitioners (PNPs) working with mental health care users presenting with acute symptoms work in a complex environment. This environment is characterised by mental health care users who may present with a history of violence, sexual assault and substance misuse. The objectives of this study were twofold: firstly, to explore and describe the experiences of PNPs working with mental health care users (MHCUs) presenting with acute symptoms; and secondly, to make recommendations for the advanced PNPs to facilitate promotion of the mental health of PNPs with reference to nursing practice, research and education. A qualitative, explorative, descriptive and contextual design was used. The target population was PNPs working with MHCUs presenting with acute symptoms in a public mental health care institution in Gauteng. Data were collected by means of four focus group interviews involving 21 PNPs. The researcher made use of drawings, naïve sketches and field notes for the purpose of data triangulation. Data were analysed in accordance with Tesch's method of open coding. The three themes that emerged were: PNPs experienced working with these MHCUs as entering an unsafe world where care became a burden; they experienced negative emotional reactions and attitudes towards these MHCUs that compromised quality nursing care; and they made a plea for a nurturing environment that would enhance quality nursing care. The PNPs suggest skills and competency development, organisational support, and a need for external resources. Creation of a positive environment and mobilisation of resources as well as the identification and bridging of obstacles are essential in the promotion of the overall wellbeing and mental health of PNPs.